Rural granaries in northern Gaul (6th century BCE-4th century CE) : from archaeology to economic history - Martin, Stéphane, 1985- (Radboud Studies in Humanities, 2019)
In recent years, storage has come to the fore as a central aspect of ancient economies. However studies have hitherto focused on urban and military storage. Although archaeological excavations of rural granaries are numerous, their evidence has yet to be fully taken into account. Such is the ambition of Rural Granaries in Northern Gaul (Sixth Century BCE - Fourth Century CE) . Focusing on northern Gaul, this volume starts by discussing at length the possibility of quantifying storage capacities and, through them, agrarian production. Building on this first part, the second half of the book sketches the evolution of rural storage in Gaul from the Iron Age to Late Antiquity, setting firmly archaeological evidence in the historical context of the Roman Empire.